1982
DOI: 10.1128/jvi.41.1.258-264.1982
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of monoclonal antibodies against the Epstein-Barr virus membrane antigen

Abstract: Five murine hybridoma lines that produce monoclonal antibodies against Epstein-Barr virus membrane antigen (MA) were established. Immunoprecipitation experiments demonstrated that three of the antibodies precipitated both the 236,000 (236K) MA and the 212K MA. The other two antibodies precipitated the 86K MA. Antibodies against the 236K-212K MA and the 86K MA mediated complement-dependent cytolysis of Epstein-Barr-virus-infected cells. The antibodies against the 86K MA neutralized both the B95-8 and P3HR-1 vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 18 publications
1
48
1
Order By: Relevance
“…Previous studies demonstrated that monoclonal antibodies directed against herpes simplex virus types 1 and 2 (2,3,32,34,54), human cytomegalovirus (33), Epstein-Barr virus (46), varicella-zoster virus (15,27), and pseudorabiesvirus (18) can precipitate several polypeptides with different electrophoretic mobilities. Because a similar phenomenon occurred with BHV-1, several approaches were used to analyze the relationships among those BHV-1 glycoproteins that appeared to be complexed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that monoclonal antibodies directed against herpes simplex virus types 1 and 2 (2,3,32,34,54), human cytomegalovirus (33), Epstein-Barr virus (46), varicella-zoster virus (15,27), and pseudorabiesvirus (18) can precipitate several polypeptides with different electrophoretic mobilities. Because a similar phenomenon occurred with BHV-1, several approaches were used to analyze the relationships among those BHV-1 glycoproteins that appeared to be complexed.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies E1D1 and F-2-1 were gifts from L. Hutt-Fletcher (Louisana State University Health Sciences Center, Shreveport, La.) and recognize the gH/gL complex and gp42, respectively (1,44). A large-scale preparation of the E1D1 and the F-2-1 antibodies was made at the Northwestern University Monoclonal Antibody Facility.…”
Section: Methodsmentioning
confidence: 99%
“…The gp92 and gp83 species seem to represent the mature virion polypeptides, as deduced by their overrepresentation relative to gp55 in virions. It is noteworthy that monoclonal antibodies to gC detect more than one glycoprotein, an observation that has been made in other members of the herpesvirus family, e.g., herpes simplex virus (4,8,23), Epstein-Barr virus (9,28), and cytomegalovirus (22). Since these cross-reactions do not appear to be nonspecific in nature, the multiple polypeptide forms could be processed from related but distinct precursors, could share pulse-chase relationships, or could represent heterogeneities in glycosylation patterns.…”
mentioning
confidence: 89%